Resiliensi Pasien Diabetes Mellitus Tipe 2 dalam Menjalani Diet di Wilayah Kerja Puskesmas Madurejo - Zuliya Indah Fatmawati; Wahyudi Qorahman MM; Eko Budi Laksono (Sahabat Publikasi Kuu, 2024)
Diabetes mellitus is a degenerative disease that is currently experienced by many in developing countries and is found in many countries in the world. Diet for diabetes mellitus is a non-pharmacological management that often creates a feeling of boredom, so the resilience of diabetes mellitus patients needs to be considered. The aim of this study was to determine the level of resilience of type 2 diabetes mellitus patients in undergoing a diet. The research results showed that 57.39% of respondents had good resilience, 34.2% had sufficient resilience and 7.9% had less resilience. Most of the respondents in this study were female with a percentage of 52.6% and the majority of respondents' last education was high school with a percentage of 44.73%. The results of this study concluded that the majority of respondents had good resilience and it still needs to be improved to minimize the risk of complications, both macrovascular and microvascular.